Case Report: Arthroscopic “Debridement Antibiotics and Implant Retention” With Local Injection of Personalized Phage Therapy to Salvage a Relapsing Pseudomonas Aeruginosa Prosthetic Knee Infection - Ferry, Tristan; Kolenda, Camille; Batailler, Cécile; Gaillard, Romain; Gustave, Claude-Alexandre; Lustig, Sébastien; Fevre, Cindy; Petitjean, Charlotte; Leboucher, Gilles; Laurent, Frédéric; , The Lyon BJI Study group (Frontiers in Medicine, 2021)
Bacteriophages are viruses that target specifically bacteria. They are considered to have a high potential in patients with PJI, as they have a synergistic anti-biofilm activity with antibiotics. We report here the case of an 88-year-old man (63 kg) with relapsing Pseudomonas aeruginosa prosthetic-knee infection. The patient had severe alteration of the general status, and was bedridden with congestive heart failure. As prosthesis explantation and/or exchange was not feasible, we proposed to this patient the use of phage therapy to try to control the disease, as compassionate therapy, in accordance with the local ethics committee and the French National Agency for Medicines and Health Products Safety (ANSM). Three phages, targeting P. aeruginosa were selected based on their lytic activity on the patient’s strain (Phagogram). The Hospital pharmacist assembled extemporaneously the cocktail of the active phages (1 ml of 1x1010 PFU/ml for each phage) as “magistral” preparation (final dilution 1x109 PFU/mL). Conventional arthroscopy was performed and 30cc of the magistral preparation was injected through the arthroscope (PhagoDAIR procedure). The patient received intravenous ceftazidime and then oral ciprofloxacin as suppressive antimicrobial therapy. The patient rapidly improved with disappearance of signs of heart failure and pain of the left knee. During the follow-up of one year, the local status of the left knee was normal and its motion, as well as walking, were unpainful. The present case suggests that the PhagoDAIR procedure by arthroscopy has the potential to be used as salvage therapy for patients with P. aeruginosa relapsing PJI, in combination with suppressive antimicrobial therapy. A Phase II clinical study deserves to be performed to confirm this hypothesis.